(untitled) (Dermatology Reports, 2025)
Skin cancer (SC) is a significant public health issue, with increasing incidence rates globally. Although environmental factors such as ultraviolet (UV) exposure are recognized risk factors, the impact of metabolites on SC development has not been thoroughly examined. This study seeks to explore the causal association between metabolites and SC risks using a Mendelian randomization (MR) approach. Our analysis revealed a total of 76 metabolites associated with SC risk. Of them, leucine to N-palmitoyl-sphingosine ratio, glycerol to palmitoylcarnitine ratio, oleoyl-linoleoyl-glycerol levels, and hypotaurine-to-taurine ratio were strongly associated with SC. Notably, leucine to N-palmitoyl-sphingosine ratio and glycerol to palmitoylcarnitine ratio were linked to increased risk factors for SC. However, oleoyl-linoleoyl-glycerol levels and hypotaurine-to-taurine ratio served as the protective indicators of SC. This study highlights the potential role of metabolites in skin cancer etiology, suggesting that metabolic factors may serve as important targets for prevention and risk assessment strategies.